(untitled) (Scientific Bulletin of the MPU School for Higher Studies, 2026)
This paper analyzes successor liability in administrative improbity, with an emphasis on the changes introduced by Law No. 14.230/2021 to Law, particularly in its Article 8. The new wording restricts the liability of the successors of the dishonest agent to the obligation to repair the damage, limiting it to the value of the transferred assets and excluding the transferability of the civil fine penalty. The study assesses the compliance of this change with the principle of the non-transferability of penalties and its implications for the adequate protection of administrative probity, as well as the relevant procedural aspects. Additionally, it briefly examines the liability of legal entities in cases of corporate reorganizations, highlighting the need to align with anti-corruption legislation. Finally, the study presents the concluding remarks, synthesizing the main findings and reflections on the topic.